Determining ground reaction forces using a pressure distribution measuring system - Kraus, A.; Odenwald, S. (The Engineering of sport 7, Volume 2, 2008)
In shoe pressure measurement Systems are intended to measure the dispersion of load between the foot and the shoe. This is achieved, for example, by using insoles which contain capacitive sensors dispersed over the sole of the foot. Based on the resulting pressure distribution data there is the Option to calculate the interacting forces In the present study the accuracy of the calculated forces is detected by means of a comparison with real ground reaction forces. For that it is used the Pedar® System by novel GmbH and a Kistler® force plate. Subject- matter is the deviation of the results measured with both Systems depending on several factors, i.e. the surface texture, the number of active sensors in the measurement, the kind of load (static or dynamic) and fit of the Pedar® insoles to the shoe. The latter is analyzed in two ways, first by a comparison between barefoot and shoed measurement to reveal the proportion of error caused by the deformation of the Pedar® insoles in the foot rest, and second by comparing several insole geometries and its influence on the accuracy of the results. Finally, reasons for inexact force measurements are summarized and rated. Moreover, relevant literature regarding the validity of force values calculated by the Pedar® System is discussed and the corresponding data is critically reviewed and compared to the results of the present study. As a result there are clear dependences between accuracy of the measurement system and the hardness of surface as well as the number of activated sensors. Dynamic measurements lead to a better congruity of data because the number of active sensors is less than with static loading. Furthermore the deformation of the Pedar® insoles contains a significant potential for failure.